Fiscal efficiency in the indian federation - Jha, Raghbendra (Bombay, 1995)
Economic analysis with several layers of government has a long and distinguished tradition in public finance (For a review see King (1984)). One of the most significant issues addressed in the literature is that of proper devolution of tax/expenditure authority between different levels of government. It is typically argued that the level of government which is legislatively supe rior should have the mandate, in some sense, to treat the lower levels of government as equals. Moreover, it is argued, that there are economies of scale in collecting taxes. If states, for example, were to impose income taxes there would be considerable diffi culties in the treatment of the incomes of taxpayers who migrate across state boundaries. Similarly, the bulk of commodity taxa tion is best carried out by the central government. It is not entirely improbable that state governments, left on their own, would opt for increasing their own tax revenues even at the risk of causing considerable allocative damage at the national level. Even under present arrangements in India where the central government collects income and excise duties and states play a relatively minor role with state sales taxes, in the main, we are all familiar with instances of how these state level taxes/subsi dies have, over the years, affected location of industry and fac tors of production.
Keywords: Fiscal policy